2019
DOI: 10.5005/jp-journals-10018-1291
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cirrhosis and Cardiomyopathy

Abstract: Introduction:We investigated association of pro-BNP, troponin-I, electrocardiography (ECG) and echocardiography (ECHO) during diagnosis and identification of cirrhotic cardiomyopathy in cirrhotic patients. Materials and methods: Patients were divided into three groups as; compensated cirrhotic patients (group 1, n= 30), decompensated cirrhotic (group 2, n = 30) and control group (group 3, n = 30). ECHO, and ECG were performed, and troponin-I and levels of pro-BNP were analyzed. Results: Average age of group 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…We found that age is associated with a higher prevalence of CCM (p-value=0.0439). Findings of various studies [ 8 - 10 ] have also demonstrated that age is one of the risk factors in such patients though another study by Uyanikoglu et al [ 11 ] has shown no significant correlation between age and CCM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that age is associated with a higher prevalence of CCM (p-value=0.0439). Findings of various studies [ 8 - 10 ] have also demonstrated that age is one of the risk factors in such patients though another study by Uyanikoglu et al [ 11 ] has shown no significant correlation between age and CCM.…”
Section: Discussionmentioning
confidence: 99%
“…More often, the warning bell of CCM is ‘rung’ by QTc prolongation in electrocardiogram. A significant increase of QTc within normal limits has been found in compensated cirrhotic patients in comparison to the control group [ 11 ]. There is a strong correlation between QTc and high serum bilirubin levels and cardiac arrhythmia [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation